Analysis of differences in cigar tobacco leaves from different regions based on GC-IMS and LC-MS metabolomics techniques - Chen, Dan; Feng, Liang; Sun, Haowei; Zhong, Risheng; Wang, Chunqiong; Zhang, Xiaowei; Zhang, Ke; Bu, Ling-duo; Yang, Wanlong; Liu, Kai; Chen, Haitao; Wang, Shuqi (Frontiers in Plant Science, 2025)
This study aimed to investigate the differences in volatile compound composition and metabolites in cigar tobacco leaves from different regions of Yunnan. Cigar tobacco leaves from various regions and varieties in Yunnan were analysed using gas chromatography-ion mobility spectrometry and non-targeted metabolomics techniques. Results showed that 109 volatile compounds, including 26 esters, 17 aldehydes, 14 alcohols, 14 ketones, 9 olefins, 5 pyrazines, 4 ethers, 4 acids and 16 others, were identified in cigar tobacco leaves. Through GC-IMS analysis of volatile compounds in cigar tobacco from 10 regions, 1-methylethyl acetate, diethyl acetal, butanal, 1-hexanol, pyridine, and toluene were identified as common compounds with consistently high content across all regions. For regional characteristics, BS-Y1-1 is featured by high levels of 2,3-diethyl-6-methylpyrazine and phenylacetaldehyde; PE-Y2 shows the highest content of 3-methyl-1-pentanol; and WS-Y38 is characterised by significantly high levels of butan-2-one. These differences reflect the uniqueness of volatile components in cigar tobacco from different producing areas. The volatile compounds in Yunnan cigar tobacco leaves were greatly influenced by the origin and species, with cigar tobacco leaves from the Baoshan region differing from those in other regions. According to the Kyoto Encyclopedia of Genes and Genomes enrichment analysis, amino acid metabolism, nucleotide metabolism and glyoxylate and dicarboxylate metabolism were the main metabolic pathways, and their metabolites contributed to the formation of flavour in Yunnan cigar tobacco leaves.